The acute effects of the voluntary pre-activity hyperventilation on jump and sprint performance in female volleyball players - Kaçoglu, C.; Miraç Isik, M. (European Journal of Human Movement, 2017)
Objective: The purpose of the present study was to investigate the acute effects of pre-activity brief maximal voluntary hyperventilation (HP) on the jumping and sprint performances. Methods: Fourteen young female volleyball players (16.7 ± 1.2 years; 61.1 ± 10.3 kg; 173 ± 8 cm) voluntarily participated in this study. All subjects performed 30s HP protocol followed by 30s passive rest. After the rest period, participants applied jump or sprint performance. All participants practiced HP and normal ventilation (NV) conditions in each test sections and conditions on separate days. Paired sample T-test was used to determine whether there was a significant mean difference between performance values with HP condition compared to NV. Results: The results of the analyses showed that there were significant differences in 10-m sprint times between HP and NV (p<0.05). However, no significant differences were determined in countermovement jump, squat jump heights and 20-m sprint time between conditions. Conclusion: The findings of the present study suggested that the pre-activity HP protocol can be effective for 10-m sprint time in moderately trained young female volleyball players. These results indicated that pre-activity HP may be useful to enhance acute athletic performance or training effectiveness.